Francesca - Oelschlager, Vanita; Blanc, Mike ([Akron, Ohio] : VanitaBooks, 2008)
A young girl named Francesca dreams impatiently about being a grown up, but after her next-door neighbor Mrs. Pinkler reminds Francesca about all the wonderful things she would miss out on if she were an adult right away.
2.3
K-3
Keywords: Adulthood -- Juvenile fiction; Girls -- Juvenile fiction; Imagination -- Juvenile fiction; Adulthood -- Fiction; Girls -- Fiction; Imagination -- Fiction; Stories in rhyme; Adults -- Fiction; Girls -- Fiction; Imagination -- Fiction; Stories in rhyme